2008
DOI: 10.2174/1874387000802010016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lower-Extremity and Trunk Muscle Fatigue on Balance

Abstract: Objective: To examine the impact of lower-extremity and trunk muscle fatigue on static and dynamic balance tests. Methods: An isokinetic dynamometer at constant angular velocities of 60°/s, 90°/s, 120°/s, and 180°/s was used to test the isokinetic strength of knee and trunk muscles in 30 healthy sedentary volunteers (14 men and 16 women). Lowerextremity fatigue was produced with the StairMaster, and trunk muscle fatigue was produced with an isokinetic dynamometer. Static and dynamic balance measurements were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…However, the mechanism of how fatigue affects balance is not fully understood. Cetin et al (2008) proposed that the afferent feedback system may be interrupted, and conscious joint awareness is altered. Another study also suggested that fatigue seems to have an effect on active joint reposition sense 16) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanism of how fatigue affects balance is not fully understood. Cetin et al (2008) proposed that the afferent feedback system may be interrupted, and conscious joint awareness is altered. Another study also suggested that fatigue seems to have an effect on active joint reposition sense 16) .…”
mentioning
confidence: 99%
“…Biomechanical deviations of the lower extremity occur during movement of the center of mass away from the base of support 14) . Balance is gained by maintaining equilibrium in a gravitational field and the ability to react quickly yet efficiently manners toward destabilizing forces to regain stability via postural adjustments 15) . Notwithstanding, these abilities are compromised during fatigue.…”
mentioning
confidence: 99%
“…All tests were performed for concentric muscle strength as well, where the maximum PT (Nm) was recorded at each angular velocity. 15 …”
mentioning
confidence: 99%
“…However, a reduction in the ability of the musculoskeletal system to respond quickly to the forces that act on the body and hinder its balance may affect perceptual and effector mechanisms and thus alter the response of the neuromuscular system, resulting in interference with body stability 18,19 . According to certain studies, trunk and lower limb muscle fatigue in young adults is associated with a reduction in postural control 11,20 .…”
Section: Introductionmentioning
confidence: 99%